The Impact of Climate Change on High‐Priority Areas of Conservation for Amphibians in North American Drylands - Jared E. Johnson; Heather L. Bateman; Adam Stein; Fábio Suzart de Albuquerque (Journal of Biogeography, 2025)
Aim The goals of this study were to (1) identify how climate change impacts the distribution of amphibian species and high‐priority conservation areas (HPCA) in the drylands of the Southwest United States and Northern Mexico, (2) describe the relationship between environmental variables and spatial configurations of HPCA and (3) explore how climate change will impact the distribution of HPCA and investigate the relationship between HPCA and protected area (PA) network. Location Southwest United States and Northern Mexico. Taxon Amphibians. Methods We used distribution maps for 209 amphibian species to estimate surrogates of amphibian diversity, assessed by rarity‐weighted richness (RWR), site importance (Zonation) and species richness. Then, we used species accumulation curves to assess their efficiency in representing amphibians in the least number of sites. Next, we used the most effective surrogate to identify HPCA for amphibians. We used environmental variables, usually related to amphibian distribution, and random forest models to assess the impact of climate on the spatial configuration of HPCA in the current and future times. We also used PA networks to assess their representation. Results RWR produced a similar spatial configuration of HPCA as Zonation but could not depict the same level of connectivity. HPCAs were observed mainly across California, central Texas and western Mexico. The spatial distribution of HPCA was mostly influenced by precipitation, temperature and solar radiation. Climate change will influence the future distribution of HPCA. The overlay between HPCA and PA is weak. Main Conclusion Climate change is becoming an ever‐increasing issue for conservation efforts, especially in dryland ecosystems where natural resources are already scarce for native species. Results show an alteration in the spatial configuration of amphibian HPCA, and much is still needed to protect and manage them.